ANALYSIS OF FACTORS AFFECTING LABOR ABSORPTION AND COMMUNITY WELFARE IN BALI PROVINCE - Putri Dwi Puspita; Ni Nyoman Yuliarmi, Ni Ketut Budiningsih, Made Kembar Sri Budhi (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
In order to reduce unemployment and boost community well-being, it is necessary to boost labor absorption because the high unemployment rate hinders national development. One of the factors that influences increasing labor absorption and community welfare is the minimum wage level, Regional Original Income (PAD), government spending, economic growth and investment. The objectives of this research are: 1) to examine the impact of the lowest pay permitted by law levels, PAD, government spending, economic growth and speculation on work assimilation in Bali Region; 2) analyze the influence of minimum wage levels, PAD, government spending, economic growth, investment and labor absorption on community welfare in Bali Province; and 3) analyze the indirect influence of minimum wage levels, PAD, government spending, financial development and speculation on local area government assistance through work retention in Bali Area. The research method used is non-participant observation. This research uses panel data with a total of 108 observations and uses path analysis techniques. Based on the analysis results, it was found that: 1) minimum wage levels, PAD, government spending, economic growth and investment have a positive and significant effect on labor absorption in Bali Province; 2) PAD, government spending, economic growth, investment and labor absorption have a positive and significant effect on the welfare of the people in Bali Province; 3) the minimum wage level does not have a positive and significant effect on the welfare of the people in Bali Province; and 4) there is an indirect influence on the level of minimum wages, PAD, government spending, economic growth and investment on community welfare in Bali Province in 2011-2022 through labor absorption. It is hoped that the government can create policies to overcome the still high unemployment rate so that the welfare conditions of its people can continue to improve.